Hooking efficiencies of SMART drumlines and their possible deployment rates vs gillnets for bather protection - Butcher, Paul A.; Broadhurst, Matt K.; Peddemors, Victor M.; McGarty, Aidan J.; Cullis, Brian R. (Frontiers in Marine Science, 2025)
IntroductionFor 87 years, gillnets have been deployed off up to 51 beaches in New South Wales, Australia, to reduce bites on humans by white (Carcharodon carcharias), bull (Carcharhinus leucas), and tiger (Galeocerdo cuvier) sharks. Recently, to minimise unwanted fishing mortalities, baited drumlines with electronic catch sensors, called ‘shark management alert in real time’ (SMART) have been trialled. The SMART drumlines are more selective than gillnets and because catches are quickly removed (with target sharks spatially displaced), nearly all survive. Nevertheless, important questions remain unanswered, including (1) the required number of SMART drumlines at a beach and (2) their risk of not being deployed due to adverse weather—which doesn’t affect gillnets.MethodsTo answer the first question, we analysed 22,025 diurnal SMART drumline deployments across 1637 days for the frequency of proximal captures (i.e. ≥two target sharks caught in similar space and time) and dependence on the number of SMART drumlines. The second question was investigated by collating weather conditions during 31 years of target-shark catches (290 white sharks and 93 tiger sharks) in gillnets and correlating these to the known operational limitations of SMART drumlines.ResultsAmong 494 hooked sharks, 71% were targets (298 whites, 43 tigers, and 9 bulls). No multiple daily catches were recorded for bull or tiger sharks, but there were 46 instances where up to five white sharks were caught off the same beach on the same day, with twenty occurrences within five km and 60 min of initial capture. Proximal captures remained independent of the number of deployed SMART drumlines or the region. The historical gillnet data revealed adverse weather would have restricted deploying SMART drumlines to 67–83% of the period gillnets were deployed, and up to ~75% of those occasions when white and tiger sharks were gillnetted.ConclusionWhile we acknowledge there would be fewer water users during adverse sea conditions, if SMART drumlines replace gillnets, their greater catching efficiency, selectivity, and survival of released animals need to be rationalised against fewer temporally comparable deployments. If the latter is acceptable, we recommend at least two or three SMART drumlines per beach to ensure a baited hook remains in the water while others are checked.